A review of non-fungicidal approaches for the control of apple scab - Carisse, O.; Dewdney, M. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2002)
Apple scab is the single most important disease of apple in Canada and the most costly to control. Failure to control apple scab results in severe yield losses and a reduction in market value of harvested fruits. Currently, the strategy to control apple scab relies on multiple applications of fungicides. These sprays are a significant cost to growers and the indirect environmental impact may be substantial. Reliance on fungicides can be reduced by the integration of non-fungicidal control measures that include genetic, physical, and biological approaches. Recommendations for chemical control of apple scab are often based on the highly susceptible cultivar McIntosh. This was justified because up to 60 to 70% of orchards in northeastern North America were planted with this cultivar. Today, the situation is changing as more and more growers are planting new cultivars, some of which are less susceptible to apple scab. A change in the recommendations to account for cultivar susceptibility could result in a reduction in the number of fungicide applications required. In addition, there has been long-standing research on resistant cultivars, but none of the scab-resistant cultivars have been widely accepted. However, with new molecular techniques to identify and locate the resistance genes, there is potential for progress on this front. Furthermore, fungicide applications for primary infections can be delayed if the number of ascospores is reduced after fall treatments that include leaf shredding, the application of biological control agents, or urea. These methods are preventive and can be integrated into existing management programs. However, the integration of all or some of these methods is more complex than simply the use of fungicides. Nevertheless, integrated management of apple scab may prove more sustainable on a long-term basis, mainly because it does not depend on the use of a single method. Hence the risk of the development of fungicide resistance in the pathogen population is reduced.